ENHANCING STUDENTS' UNDERSTANDING AND APPLICATION OF PHYSICS THROUGH STEM-BASED LEARNING - Miswatul Hasanah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Science, Technology, Engineering, and Mathematics (STEM) education has gained significant attention in recent years, particularly in the context of enhancing learning outcomes and fostering critical thinking. This study investigates the implementation of STEM-based learning strategies in physics education, focusing on how these interdisciplinary approaches influence students' understanding of complex physical concepts. By integrating hands-on experiments, real-world applications, and collaborative problem-solving, STEM education in physics aims to bridge the gap between theoretical knowledge and practical skills. The study uses a case study methodology to examine the impact of STEM activities on student engagement, comprehension, and application of physical principles. Results indicate that STEM-based instruction fosters deeper understanding, improves retention of core concepts, and enhances students' ability to apply their knowledge in real-world scenarios. This paper discusses the challenges and benefits of incorporating STEM strategies in physics education, offering insights into its potential to transform traditional teaching methodologies and prepare students for the demands of a technology-driven future.